2018
DOI: 10.2147/copd.s158031
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations of the prevalence and distribution of COPD phenotypes in Spain: “the ESPIRAL-ES study”

Abstract: PurposeThe purpose of this study was to assess the prevalence of COPD phenotypes at a national level and to determine their geographic distribution among different autonomous communities in Spain.Patients and methodsA total of 1,610 patients (82% men, median age 67 years) recruited in primary care centers and pneumology services participated in an observational, cross-sectional, and multicenter study. Phenotypes evaluated were the non-exacerbator phenotype, the asthma–COPD overlap syndrome (ACOS), the exacerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
5
13
0
7
Order By: Relevance
“…The rst study was conducted in the primary care centres of the Russia Federation, (29) while the second study involved selected COPD patients in the respiratory clinic of a tertiary hospital. (30) Our ndings of patients with AE being older and smoked more cigarettes, (25,27,28,31) as well as more female with the ACO phenotype are in agreement with other studies. (24,(26)(27)(28) The nding that the HRQoL of COPD patients was more impaired in the sequence of NON-AE, ACO and AE is consistent with the ndings of previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The rst study was conducted in the primary care centres of the Russia Federation, (29) while the second study involved selected COPD patients in the respiratory clinic of a tertiary hospital. (30) Our ndings of patients with AE being older and smoked more cigarettes, (25,27,28,31) as well as more female with the ACO phenotype are in agreement with other studies. (24,(26)(27)(28) The nding that the HRQoL of COPD patients was more impaired in the sequence of NON-AE, ACO and AE is consistent with the ndings of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of COPD phenotypes in the present study was almost similar to western populations, (24)(25)(26)(27) except the AE NON-CB was reported less than ACO. (28) So far, only two study reported AE CB was the commonest COPD phenotypes followed by NON-AE, AE NON-CB and ACO.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…(24, 26 -28, 32) Patients with AE are consistently highlighted as having the worst HRQoL, (24, 26 -28, 31, 32) while those with NON-AE have the best HRQoL. (25,29) Of patients with AE, Miravitlles et al, (28) Cosio et al,(31) Kania et al, (27) and Chai et al, (30) reported those with AE-CB have signi cantly worse HRQoL compared to other COPD phenotypes (all p < 0.001); while Corlatenau et al reported the worst HRQoL in patients with AE NON-CB. (32) The CAT was uniformly used to asses HRQoL in these studies, with the latter two studies also using the SGRQ-c questionnaire.…”
Section: Discussionmentioning
confidence: 98%
“…(24,(26)(27)(28)32) Patients with AE were constantly highlighted as having the worst HRQoL, (24, 26-28, 31, 32) while those with NON-AE had the best HRQoL. (25,29) Of patients with AE, Miravitlles et al, compared to other COPD phenotypes (all p < 0.001); while Corlatenau et al reported the worst HRQoL in patients with AE NON-CB. (32) CAT was uniformly used to asses HRQoL in these studies, with the latter two studies also added on SGRQ-c. Only this study and that by Miravitlles et al, (28) show patients with ACO had signi cantly worse HRQoL than those with NON-AE.…”
Section: Discussionmentioning
confidence: 99%